Desa Cerdas Ramah Gender: Analisis Penerapan Sertifikasi Halal dan Komersialisasi Produk Bagi Pelaku UMKM Perempuan - Fawaid, Achmad; Abdullah, Abdullah (LABATILA : Jurnal Ilmu Ekonomi Islam, 2024)
The idea of ​​a smart village has become a fundamental instrument in the policy framework of the Ministry of Villages, Development of Disadvantaged Regions and Transmigration (Kemendes PDTT) of the Republic of Indonesia. However, the way this idea is integrated with halal certification and commercialization of local products to develop gender-friendly smart village at the micro level has lack of attention. This research aims to analyze the implementation of gender-friendly smart villages in industrial areas on Java’s toll roads through certification and commercialization of local products. The intervention was carried out specifically in Clarak, a village on the outskirts of Probolinggo, which is directly adjacent to the Probowangi toll road. The case study, involving 30 female MSME actors, focuses on how halal certification and product commercialization can increase their participation in the Gender-Friendly Smart Village (DCRG). This research identified at least 6 (six) assets owned by Clarak in initiating a gender-friendly smart village, namely individual assets, physical assets, institutional assets, network assets, local economic assets and historical assets. This research also figures out that there is an increase in women’s participation as beneficiaries of this program as well as an increase in digital knowledge regarding the commercialization of local products. This research contributes to similar research that seeks to understand how the smart village concept is initiated at the micro level, especially in industrial areas.